Membangun Personal Branding di Linkedin: Perspektif Generasi Z dalam Pencarian Kerja - Rahmawati, Fanneza; Wijaya, Lina Sinatra (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Generation Z is a generation that grows up with technology. Along with the rapid development of technology, everything has been modernized, as well as in the career world that currently has taken advantage of LinkedIn. Generation z must be able to compete in using LinkedIn by showing strong personal branding. This is because the fierce competition for jobs makes every individual must be able to compete to get a job they want. Thus, before entering the world of career, the thing that must be done by generation z is to prepare as best as possible. The same thing was also done by students of Satya Wacana Christian University (UKSW) who are classified as generation z. Students take advantage of linkedin social media to prepare for their careers. This research aims to find out personal branding on Linkedin social media in the view of generation Z to find a job. This study uses a descriptive qualitative method to obtain data through interviews with 10 resource persons from various faculties and departments at UKSW. The results of the study show that UKSW final semester students have understood that content creation on linkedin must be in accordance with the personal branding criteria, namely Authenticity, Integrity, Consistency, Specialization, Authority, Distinctiveness, Relevant, Visibility, Persistence, Goodwill and Performance. With this strategy, it can increase the opportunity to get a job during existing competition. Generasi Z merupakan generasi yang tumbuh bersama dengan teknologi. Seiring dengan pesatnya perkembangan teknologi menjadikan semua hal mengalami modernisasi, begitu pula dalam dunia karir yang saat ini telah memanfaatkan linkedin. Generasi z harus mampu bersaing dalam menggunakan linkedin dengan memperlihatkan personal branding yang kuat. Hal ini dikarenakan ketatnya persaingan kerja menjadikan setiap individu harus mampu bersaing untuk mendapatkan suatu pekerjaan yang diinginkan. Dengan demikian sebelum terjun ke dunia karir, hal yang harus di lakukan oleh generasi z yaitu dengan mempersiapkan diri sebaik mungkin. Hal serupa juga turut dilakukan oleh mahasiswa Universitas Kristen Satya Wacana (UKSW) yang tergolong kedalam generasi z. Mahasiswa memanfaatkan media social linkedin untuk mempersiapkan karir. Penelitian ini bertujuan untuk mengetahui personal branding pada media social Linkedin dalam pandangan generasi Z untuk mencari pekerjaan. Penelitian ini menggunakan metode kualitatif deskriptif untuk memperoleh data melalui wawancara terhadap 10 narasumber yang berasal dari berbagai fakultas dan jurusan di UKSW. Hasil penelitian menunjukkan bahwasanya mahasiswa semester akhir UKSW telah memahami bahwa dalam pembuatan konten di linkedin harus sesuai dengan kriteria personal branding yaitu Authenticity, Integrity, Consistency, Specialization, Authority, Distinctiveness, Relevant, Visibility, Persistence, Goodwill dan Performance. Dengan adanya strategi tersebut, dapat memperbesar peluang untuk mendapatkan pekerjaan di tengah persaingan yang ada.